The Relevance Challenge in Management and Organization Studies: Bringing Organization Development Back In. (December 2020) - Cummings, Thomas G.; Cummings, Chailin
We address management and organization studies' (MOS) mounting relevance challenge of creating knowledge that matters far more to researchers than practitioners. Organization development (OD), a subfield of MOS, can help bridge the research–practice gap. OD was once a valued contributor to MOS creating applied knowledge to change and improve organizations. Yet that contribution gradually diminished and today OD is a marginal member of the MOS community. A historical–evolutionary analysis reveals the causes for that decline and suggests how to bring OD back in to address the relevance challenge. Our proposal involves the application of OD action research, an engaged and collaborative form of inquiry that creates knowledge in the service of helping organizations improve themselves.